The use of selected phytochemicals with EDTA against Escherichia coli and Staphylococcus epidermidis single- and dual-species biofilms - J. Vale (2019)
The aim of this study was the development of a novel and effective antibacterial formulation combining selected phytochemical compounds (quercetin, cuminaldehyde, indole-3-carbinol and vanillic acid) with ethylenediaminetetraacetic acid (EDTA), an aminopolycarboxylic acid. The antibacterial activity of the combinations was evaluated against Escherichia coli and Staphylococcus epidermidis in planktonic and sessile states as single and dual species. The compounds when applied individually demonstrated modest antibacterial activity. Nevertheless, synergy was observed when EDTA was combined with the selected phytochemicals, particularly with cuminaldehyde and indole-3-carbinol. These combinations were evaluated against single- and dual-species biofilms. An inactivation of 100% was obtained for almost all the biofilms, with E. coli biofilms showing the highest resistance. This study allowed the discovery of novel formulations of phytochemical compounds with antibacterial activity against E. coli and S. epidermidis single- and dual-species biofilms at concentrations close to the minimum bactericidal concentration. Significance and Impact of the Study The synergistic combinations of EDTA and cuminaldehyde or indole-3-carbinol were effective against single- and dual-species E. coli and S. epidermidis planktonic cells and biofilms. The overall results highlight the role of phytochemical products as a green and sustainable source of antimicrobial potentiators to control bacteria in both planktonic and sessile states.